Delayed priesthood vocations - JAKUBIAK, TOMASZ (Prawo Kanoniczne, 2014)
Delayed vocations are all those vocations which do not come into the notion of so-called „normal” vocation or path of education.Holy See welcomes them as a sign of spiritual renewal among the mature. Delayed vocations call for a special formation path which may not necessarily coincide with the formation path of seminary. In spite of the fact that the mature are not obliged to receive seminary formation they are obliged to observe the norms of canons 1008-1054 CIC regarding priestly ordination. Detailed concept of so-called „mature vocations” was presented in a letter „Circular LetterVocationes adultorum”, 14 July 1974. Current law doesn’t require men willing to enter the seminary after obtaining bishop’s sentence declaring nullity of marriage to obtain any further consent or dispense. If the candidate has children they must be grown up and economically self-sufficient. Formation for „second career” applicants, seems to be best accomplished in a seminary setting which is constructed only for older candidates.